Implementasi Good Coorporate Governance Terhadap Pengelolaan Wakaf Produktif Pada RSU Haji Medan - M. Iqbal; Reni Ilma Sari; Safrina Safitri; Upik Nurhasanah (MUQADDIMAH: Jurnal Ekonomi, Manajemen, Akuntansi dan Bisnis, 2024)
This article aims to determine the implementation of Good Corporate Governance in the Management of Productive Waqf at RSU Haji Medan, which is a productive waqf managed based on the principle of accountability. These findings show that RSU Haji Medan is a large company supervised by the waqf institution and has experienced significant progress, with a significant increase in the number of customers. The Supervisory Board established the concept of accountability for the Islamic Hospital in Medan City, requiring regular supervision based on reports from the RSI Director. Stakeholder confidence is expected to increase when endowments implement these ideas. Future external audit monitoring needs to be planned to increase public trust and accountability.